Elemental composition, physicochemical properties, and calcium bioavailability of calcined gill powders from Asian seabass and catfish - Umesh Patil; Suriya Palamae; Krisana Nilsuwan; Pornsatit Sookchoo; Prabjeet Singh; Lukai Ma; Bin Zhang; Soottawat Benjakul (Food Chemistry: X, 2025)
Calcined gill powders (CGPs) from Asian seabass and catfish were prepared by calcination at 900 °C for 6 h. Seabass (SB-CGP) and catfish (CF-CGP) were characterized for their chemical composition, morphology, functional groups, and crystallinity. Cytotoxicity was assessed using BJ cells, and calcium bioavailability was compared with CaCO3 using a Caco-2 cell model. Both CGPs had high ash content (99.21–99.58 %). SB-CGP showed a larger particle size and higher crystallinity than CF-CGP. The morphological structures of CGPs from two fish species were different. Ca, P, Mg, and Na were found in both CGPs, whereas S and K were detected only in CF-CGP. Notably, the Ca/P ratio in both CGPs exceeded the standard stoichiometric ratioof 1.67. Cytotoxicity assay of both CGPs showed high cell viability at all concentrations and time used. At 4 h, SB-CGP (44.31 %) and CF-CGP (43.86 %) demonstrated superior calcium bioavailability to CaCO3 (36.24 %), suggesting their potential as alternative calcium supplementation.